2015
DOI: 10.1080/21655979.2015.1019686
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an exo-inulinase fromArthrobacter: A novel NaCl-tolerant exo-inulinase with high molecular mass

Abstract: (2015) Characterization of an exo-inulinase from Arthrobacter: A novel NaCl-tolerant exo-inulinase with high molecular mass, Bioengineered, 6:2, 99-105, DOI: 10.1080/21655979.2015 Keywords: Arthrobacter, exo-inulinase, lead, NaCl, zinc A glycoside hydrolase family 32 exo-inulinase gene was cloned from Arthrobacter sp. HJ7 isolated from saline soil located in Heijing town. The gene encodes an 892-residue polypeptide with a calculated mass of 95.1 kDa and a high total frequency of amino acid residues G, A, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The exo-inulinases from Arthrobacter strains HJ7 and MN8 and Sphingomonas sp. JB13 were observed to exhibit considerable salt tolerance, without a clear elucidation of structural characteristics and mechanisms regarding salt tolerance ( Shen et al, 2015 ; Zhou et al, 2015a , b ). Comparisons of biochemical and structural properties among InuAMN8 and its mutants MutG169Δ4 and MutG360Δ9 in this study revealed that salt tolerance showed a positive correlation with the negatively charged surface.…”
Section: Discussionmentioning
confidence: 99%
“…The exo-inulinases from Arthrobacter strains HJ7 and MN8 and Sphingomonas sp. JB13 were observed to exhibit considerable salt tolerance, without a clear elucidation of structural characteristics and mechanisms regarding salt tolerance ( Shen et al, 2015 ; Zhou et al, 2015a , b ). Comparisons of biochemical and structural properties among InuAMN8 and its mutants MutG169Δ4 and MutG360Δ9 in this study revealed that salt tolerance showed a positive correlation with the negatively charged surface.…”
Section: Discussionmentioning
confidence: 99%
“…This inulinase can sustain 90% of its activity during one hour incubation at 50°С. Shen et al (2015) found that the exoinulinase from Arthrobacter sp. HJ7 has a temperature optimum range of 40-45°С and a pH optimum ranging between pH 5.0 and 5.5.…”
Section: Temperature Optimum and Temperature Stabilitymentioning
confidence: 97%
“…Cu 2+ , Zn 2+ and Ni 2+ also inhibit said inulinase. Shen et al (2015) determined that the exo-inulinase produced by Arthrobacter sp. HJ7 is not affected by 1.0 and 10.0 mМ Zn 2+ and Pb 2+ ions.…”
Section: Effects Of Metal Ions and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Arthrobacter can effectually utilize inorganic and organic compounds as a metabolism substrate, acting as a tool for bioremediation in agriculture [ 75 , 76 , 77 , 78 ]. Certain Arthrobacter species, mainly soil-dwelling rhizobacteria, have been considered as plant growth promoters because of their different growth-promoting activities, such as potassium and phosphate solubilization, nitrogen fixation, and indole acetic acid synthesis [ 79 , 80 ].…”
Section: Arthrobacter Sppmentioning
confidence: 99%